Developing an Instrument for Scientific Attitude Assessment In Learning Chemistry - Roshiana Maria Angelia Dewi Permata Gading; Eli Rohaeti (Jurnal Penelitian Pendidikan IPA, 2024)
A component of the learning process, attitude reflects the development and comprehension of the attitudes of individual students. The cultivation of scientific attitudes among students remains a relatively unacknowledged educational objective. The objectives of this study are as follows: (1) developing the framework of a scientific attitude assessment instrument intended for high school chemistry lesson; and (2) establishing the reliability and validity of the developed scientific attitude assessment instrument. This study performs instrument development research in the affective domain in accordance with Gable & Wolf's (1993) research procedures. The participants in this study comprised a sample of 250 high school students. The Result of this research is the Honesty factor is the most influential in this instrument; cooperation, on the other hand, has the weakest loading factor value at 0.881. The SEM model as a whole has good capabilities in terms of matching sample data (Good Fit).